Estudo da produção científIca fonoaudiológica nacional sobre família - Pereira, Alessandra da S. Cabral (2008)
Target: To rise and the characterize part of national phonoaudiological scientific production about family in the period between 1986 2006. Method: documental study which raised the publications in periodicals, thesis and dissertations, considering the following aspects: 1) publication period, 2) frequency distribution by period, 3) publication types, 4) sub-thematics (5) epistemological approach, 6) phonoaudiological area which works belongs to. Results: Family is a matter of research little explored. In the period of 20 (twenty) years investigated, we have found only 57 (fifty seven) works. The sub-thematics most approached were: Importance of Work with The Family to Phonoaudiological Therapy and Influences of Families Relations on Language Symptoms. The theme family is preferably historical dialecticaly approached. The main thematic to which searched works belong is Language. Conclusion: The research had a growth which, althought small, follows the growth of scientific production of area in general. The epistemological approach preferably chosed by researchers takes the theme family in its complexity, it means, in its dialectic movement of interaction among several factors, suggesting this is the best way to understand it. Maybe there is a relation between the little research productions in such an important theme with the lack of knowledge by searchers in handling research in a dialectical historical approach